Basic Beliefs and Feelings of Youth Facing Ecological Collapse - González-Anleo, Juan María; Barbero Alcocer, Irene (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2023)
A sufficiently energetic change, especially on the part of the youth, that can truly save us from a present that increasingly appears as the first in history without a future, must be a radical change in the profound etymological sense of this word - a change that affects the roots of our ecological consciousness. Many times, too many times, we take for granted that the youth are at the forefront of this copernican shift in our relationship with nature. our research shows that there are many more nuances than one might pre sume, and far from having deeply penetrated the younger generation, environmental awareness within this demographic is only just beginning.